2013
DOI: 10.1037/a0030160
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, self-regulated learning, and achievement in mathematics: A growth curve analysis.

Abstract: The purpose of the current study was twofold; (a) to investigate the developmental trends of 4 academic emotions (anxiety, boredom, enjoyment, and pride) and (b) to examine whether changes in emotions are linked to the changes in students' self-regulatory strategies (shallow, deep, and meta-cognitive) and achievement in mathematics. Four hundred and ninety-five Grade 7 students completed measures assessing their emotions and self-regulatory strategies in mathematics 3 times across 3 terms in a school year. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
180
6
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(243 citation statements)
references
References 66 publications
23
180
6
19
Order By: Relevance
“…Despite its being negative, its activating nature made students engage into deep learning approach to deal with the negative outcomes the emotion brings along [6]. These findings are consistent with the previous studies where negative activating emotions were found to associate with deep and metacognitive strategy use [6,28]. Interestingly, all other negative emotions did not predict the four variables of value, expectancy, cognitive, and resource management.…”
Section: Emotions and Learning Strategiessupporting
confidence: 82%
See 1 more Smart Citation
“…Despite its being negative, its activating nature made students engage into deep learning approach to deal with the negative outcomes the emotion brings along [6]. These findings are consistent with the previous studies where negative activating emotions were found to associate with deep and metacognitive strategy use [6,28]. Interestingly, all other negative emotions did not predict the four variables of value, expectancy, cognitive, and resource management.…”
Section: Emotions and Learning Strategiessupporting
confidence: 82%
“…One of the most striking outcomes of the study is that, despite differences in some of the emotions, there were no significant differences on learning strategies among all four programs and on gender. These findings are contrary to the previous studies [6,14,19,28] and the theoretical assumption [14] which affirms that students with positive emotions would be more motivated to facilitate their SRL and eventually would resort to a wider range of strategy use. According to the control-value theory, male students in this study would have shown a wider range of strategy use due to their positive emotions' role on SRL strategies than female students.…”
Section: Students' Srl Strategiescontrasting
confidence: 56%
“…Overall, the results of our preliminary cross-lagged analyses provide support for Hypothesis 1 in showing achievement goals to more significantly predict subsequent emotions than vice versa (i.e., performance-avoidance goals and negative emotions), but do not support Hypothesis 2 concerning the effects of emotions on learning strategies. However, as the present findings do not alternatively show effects of learning strategies on emotions, likely due to the highly stable nature of these constructs over time, these findings do not preclude our evaluation of hypothesized effects of emotion on learning in subsequent mediational models as supported by Pekrun's control-value theory and existing research on emotions and learning outcomes (e.g., Ahmed et al, 2013;Artino & Jones, 2012;Pekrun et al, 2002Pekrun et al, , 2010Pekrun et al, , 2011.…”
Section: Cross-lagged Modelsmentioning
confidence: 62%
“…Interestingly, the link between ones' emotions and selfregulated learning has received considerably less empirical attention, despite several theoretical models of self-regulated learning in which learning-related emotions are explicitly incorporated (i.e., Efklides, 2011;Pintrich, 2004;Winne & Hadwin, 1998;Zimmerman, 2000). Nevertheless, recent empirical work has shown enjoyment and anxiety to predict learning strategies (e.g., elaboration, rehearsal, problemsolving) and self-regulated learning (e.g., selfmonitoring, planning) in the expected directions (Ahmed, van der Werf, Kuyper, & Minnaert, 2013;Goetz et al, 2006;Pekrun et al, 2011;Pekrun et al, 2002;Villavicencio & Bernardo, 2013), with boredom having also been found to predict poorer elaboration and self-regulated learning (Artino & Jones, 2012;Pekrun et al, 2002Pekrun et al, , 2010.…”
Section: Achievement Emotionsmentioning
confidence: 99%
“…The most important thing is how to follow up the result obtained through the assessment to improve learning. Ahmed in [34] finds out that change in emotion and learning correlates positively with mathematics learning achievement. Similarly, Mulyaningsih in [35] also shows that learning autonomy has a significantly positive effect on the students' learning autonomy.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%